2019
DOI: 10.1002/iub.2151
|View full text |Cite
|
Sign up to set email alerts
|

Activation of GPR81 by lactate inhibits oscillatory shear stress‐induced endothelial inflammation by activating the expression of KLF2

Abstract: Atherosclerosis is a common and deadly cardiovascular disease with extremely high prevalence. Areas of the vasculature exposed to oscillatory shear stress (OSS) or disturbed blood flow are particularly prone to the development of atherosclerotic lesions. In part, various mechanosensitive receptors on the surface of endothelial cells play a role in regulating the ability of the vasculature to cope with variations in blood flow patterns. However, the exact mechanisms behind flow-mediated endothelial responses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 39 publications
(38 reference statements)
1
17
1
Order By: Relevance
“…Some of the pathways such as oxidative stress and inflammation are overall up-regulated by OS vs. PS, i.e., most genes in these pathways are up-regulated. Some of these findings are in agreement with other previous results on HUVECs, e.g., Sun et al (38) have shown that OS increased gene and protein expressions for VCAM1 and SELE and levels of mitochondrial ROS, and Hsu et al (39) have reported similar findings. Gene expressions of VCAM1, ICAM1, and MCP1 have been shown to increase in OS vs. PS in HAECs [Brooks et al (40)] and HUVECs [Fan et al (41)].…”
Section: Kinetics Of Shear Stresssupporting
confidence: 91%
“…Some of the pathways such as oxidative stress and inflammation are overall up-regulated by OS vs. PS, i.e., most genes in these pathways are up-regulated. Some of these findings are in agreement with other previous results on HUVECs, e.g., Sun et al (38) have shown that OS increased gene and protein expressions for VCAM1 and SELE and levels of mitochondrial ROS, and Hsu et al (39) have reported similar findings. Gene expressions of VCAM1, ICAM1, and MCP1 have been shown to increase in OS vs. PS in HAECs [Brooks et al (40)] and HUVECs [Fan et al (41)].…”
Section: Kinetics Of Shear Stresssupporting
confidence: 91%
“…16 Single-cell RNA sequencing detected GPR81 in cerebral and lung vascular smooth muscle cells. 18 GPR81 has been identified in cultured human umbilical vein endothelial cells, 19 but we suggest this is not a major expression site, finding discernable levels in only 1 of 4 isolated renal endothelial cell samples and no in situ endothelial GPR91 mRNA expression in large arteries. Similarly, GPR81 does not co-localize with endothelial cell markers in the cerebral vasculature.…”
Section: Discussioncontrasting
confidence: 53%
“…It was also found that activation of GPR81 reduced the expression of Kruppel-like factor-2 (KLF2), a key atherosclerotic protective transcription factor induced by OSS. These findings suggested that GPR81 had a potential protective effect on atherosclerosis and targeting GPR81 may inhibit OSS-induced endothelial inflammation and dysfunction [99]. In 2020, KunYang discovered a new mechanism, found that lactic acid inhibited the activation of YAP and NF-κB during inflammation through GPR81-mediated signal transduction, and inhibited the pro-inflammatory response of macrophages stimulated by LPS [89].…”
Section: Effects Of Lactic Acid Signaling On Inflammatory Responsementioning
confidence: 99%